PENCIRIAN DAN UJI AKTIVITAS KATALITIK ZEOLIT ALAM TERAKTIVASI - Charlena -; Henny Purwaningsih; Tina Rosdiana (Jurnal Riset Kimia, 2008)
ABSTRACT Natural zeolite reserves are spread in Indonesia, but they are not yet used optimally. Generally, natural zeolite have poor crystalline, various pore size, low catalytic activity, and high contaminant. Natural zeolite need to be activated and modified before it can be used. The objectives of this research were to activite the natural zeolite that already got acid and thermal treatments and to characterize it and catalytic activity was tested in interesterification reaction. Fourier transformation infrared (FTIR) spectra showed that the structure of natural zeolite activated by acid and thermal  (NZAT) treatments were damaged. While, natural zeolite structure activated with acid (natural zeolite acid /NZA) did not show significant different to natural zeolite (NZ). Result of Si/Al ratio analysis showed that Si/Al ratio NZA higer than Si/Al ratio NZAT. The result of cation analysis by atomic absorption spectroscopy shoed that the general content of Na, K, Fe and Ca in the catalyst decreased because of acid and thermal treatments. Surface area and pore volume increased by the treatments. Catalytic activity of NZA in interesterification reaction gave a white cork product and in yield 35.78 %. Keywords : natural zeolite activated, catalytic activity, FTIR.